Issues affecting the adoption of IPv6 - Oxley, A. (Institute of Electrical and Electronics Engineers Inc., 2014)
Internet Protocol version 4 sets rules for some aspects of communication over the Internet. The protocol, amongst other things, specifies the format of an Internet Protocol address. This format places restrictions on the total number of possible addresses. In 2011 the supply of new addresses was exhausted. A new version of the standard, version 6, has been developed. This provides substantially more addresses. The intention is to replace version 4 with version 6. Organizations are deciding whether or not now is the right time to change. The change incurs an expenditure of time and money. If any of the hardware does not support the new protocol then it will have to be replaced. Also, software needs to be upgraded. A change requires a transitional phase. It is not possible to make the necessary updates to hardware and software over a weekend, say. This paper looks at the issues that are relevant to a decision to change. Â© 2014 IEEE.